The Effect Of Intellectual Capital, Profit Sharing Ratio And Financing To Deposit Ratio On The Financial Performance Of Sharia Banks - Nasution, Nina Andriany; Siregar, Saparuddin; Kamilah, Kamilah (Univeristas Islam Bandung, 2023)
The purpose of this research is to evaluate the financial performance of BPRS in North Sumatra. Specifically for the application of Intellectual Capital (IC), measurement of Profit Sharing Ratio (PSR) and measurement of Financing to Deposit Ratio (FDR) to Debt to Equity Ratio (DER) and Return On Equity (ROE). The research approach uses Quantitative with Panel Data Types from 2017 – 2021, Panel Data Multiple Linear Regression analysis techniques and Path Analysis. The results of this study are: Intellectual Capital has a positive and significant effect partially on the Financial Performance (DER, ROE) of BPRS in North Sumatra; Profit Sharing Ratio (PSR) has a positive and significant effect partially on the Financial Performance (DER) of BPRS in North Sumatra; Financing to Deposit Ratio (FDR) has a positive and significant partial effect on the Financial Performance (DER) of BPRS in North Sumatra. Intellectual Capital (IC), Profit Sharing Ratio (PSR) and Financing to Deposit Ratio (FDR) simultaneously have a positive and significant effect on the Financial Performance (DER, ROE) of BPRS in North Sumatra.